PERAN ORANG TUA URBAN DALAM MENINGKATKAN MOTIVASI BELAJAR DAN KECERDASAN EMOSIONAL SISWA DI MTS IRSYADUL ANAM TELLOK GALIS BANGKALAN - syado'i, ach (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to discuss: 1) What is Student Learning Motivation at MTs Irsyadul Anam Tellok Galis Bangkalan? 2) How is the Emotional Intelligence of MTs Irsyadul Anam Tellok Galis Bangkalan Students. 3) What is the role of urban parents in increasing learning motivation and emotional intelligence at MTs Irsyadul Anam Tellok Galis Bangkalan? This research uses a qualitative method using a phenomenological approach. Data collection techniques use observation, interviews, document review. The data analysis technique uses interactive Miles and Hiberman. The results of data analysis from this research are as follows: first, motivation theory which refers to Abraham Maslow, where motivation is a driving force for the person to do something, especially in learning activities. Urbanization is an activity that has good intentions but has a serious impact on the development of children left behind. It can be concluded by researchers that urbanization has an impact on learning motivation which shows that children have low motivation at school. Second, the emotional intelligence of students whose parents leave them abroad has several behavior patterns that are slightly inconsistent with their development, such as students who have bad behavior patterns. Third, parents who are urban or have migrated have less of a role in growing and increasing students' motivation and emotional intelligence because direct parental assistance will have a positive impact on the development of the child or student.